A influência da informação háptica do gênero e do conhecimento da categoria nas percepções de risco, qualidade e confiança - Pompeo, Karin Ligia Brondino (2013)
Marketing literature shows that need for touching products differs among individuals. The information obtained through hands – or haptic information – is important for evaluation of products. This study aims to evaluate whether need for touch (NFT) have effects on confidence in judgment, perceived product quality, and perceived risk, considering two different purchase situations: when the product is bought for oneself and when it is bought as a gift to someone else. This research also examines the moderation effect of gender and prior product category knowledge. An experiment was conducted using a convenience sample of 171 male and 153 female undergraduates students. The scales were tested using confirmatory factor analysis and they have reached satisfactory fit. The hypotheses were tested using multiple linear regression. Participants’ confidence in judgment was influenced by product knowledge and purchase situation, being higher when the product is bought for oneself. Perceived quality experienced the positive effect of product knowledge and gender – women perceive lower quality level than men. Perceived risk was influenced by purchase situation – higher when the product is bought as a gift. Results showed that NFT doesn’t have direct effect on perceived risk, but through its interaction with gender. Therefore this study didn’t find NFT direct influence on outcome variables, suggesting that other aspects could prevail over NFT during purchase decision process.